Systematic genomic analysis reveals the complementary aerobic and anaerobic respiration capacities of the human gut microbiota - Ravcheev, Dmitry A.; Thiele, Ines (Frontiers in Microbiology, 2014)
Because of the specific anatomical and physiological properties of the human intestine, a specific oxygen gradient builds up within this organ that influences the intestinal microbiota. The intestinal microbiome has been intensively studied in recent years, and certain respiratory substrates used by gut inhabiting microbes have been shown to play a crucial role in human health. Unfortunately, a systematic analysis has not been previously performed to determine the respiratory capabilities of human gut microbes (HGM). Here, we analyzed the distribution of aerobic and anaerobic respiratory reductases in 254 HGM genomes. In addition to the annotation of known enzymes, we also predicted a novel microaerobic reductase and novel thiosulfate reductase. Based on this comprehensive assessment of respiratory reductases in the HGM, we proposed a number of exchange pathways among different bacteria involved in the reduction of various nitrogen oxides. The results significantly expanded our knowledge of HGM metabolism and interactions in bacterial communities.